Funkcje motywacyjne budżetowania w przedsiębiorstwie - Dylewski, Marek (Motivation Functions in Budgeting, 2005)
Budgeting as a management tool is a dynamic process of making decisions. Company employees deliver results for their organization. It is the reason that managers want to make the best decisions. In the budgeting as a management tool team is a base of success. How to manage people for better effect? In the article there is a trial to answer to the problem of budgeting and its motivation function.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 139-146